Direct Thrombin Inhibitor Dabigatran Compromises Pulmonary Endothelial Integrity in a Murine Model of Breast Cancer Metastasis to the Lungs; the Role of Platelets and Inflammation-Associated Haemostasis - Smeda, Marta; Stojak, Marta; Przyborowski, Kamil; Sternak, Magdalena; Suraj-Prazmowska, Joanna; Kus, Kamil; Derszniak, Katarzyna; Jasztal, Agnieszka; Kij, Agnieszka; Kurpinska, Anna; Kieronska-Rudek, Anna; Wojnar-Lason, Kamila; et al. (Frontiers in Pharmacology, 2022)
Activation of the coagulation cascade favours metastatic spread, but antiplatelet/antithrombotic therapy might also have detrimental effects on cancer progression. In this study, we characterized the effects of dabigatran, a direct reversible thrombin inhibitor, on the pulmonary endothelial barrier and metastatic spread in a murine model of breast cancer metastasis. Dabigatran etexilate (100 mg ⋅ kg-1) was administered to mice twice daily by oral gavage. Pulmonary metastasis, pulmonary endothelium permeability in vivo, and platelet reactivity were evaluated after intravenous injection of 4T1 breast cancer cells into BALB/c mice. The effect of dabigatran on platelet-dependent protection of pulmonary endothelial barrier in the presence of an inflammatory stimulus was also verified in vitro using human lung microvascular endothelial cell (HLMVEC) cultures. Dabigatran-treated mice harbored more metastases in their lungs and displayed increased pulmonary endothelium permeability after cancer cell injection. It was not associated with altered lung fibrin deposition, changes in INFγ, or complement activation. In the in vitro model of the pulmonary endothelial barrier, dabigatran inhibited platelet-mediated protection of pulmonary endothelium. In a murine model of breast cancer metastasis, dabigatran treatment promoted pulmonary metastasis by the inhibition of platelet-dependent protection of pulmonary endothelial barrier integrity.